Minor Hematochezia Decreases Use of Venous Thromboembolism Prophylaxis in Patients with Inflammatory Bowel Disease. Issue 9 (5th November 2019) - Faye, Adam S; Hung, Kenneth W; Cheng, Kimberly; Blackett, John W; Mckenney, Anna Sophia; Pont, Adam R; Li, Jianhua; Lawlor, Garrett; Lebwohl, Benjamin; Freedberg, Daniel E
Abstract : Patients with IBD are less likely to be placed on pharmacologic venous thromboembolism prophylaxis, and hematochezia seems to be the major driver. Additionally, prophylaxis is not associated with evidence of increased bleeding, regardless of whether it is given in the setting of hematochezia. Abstract: Background: Despite increased risk of venous thromboembolism (VTE) among hospitalized patients with inflammatory bowel disease (IBD), pharmacologic prophylaxis rates remain low. We sought to understand the reasons for this by assessing factors associated with VTE prophylaxis in patients with IBD and the safety of its use. Methods: This was a retrospective cohort study conducted among patients hospitalized between January 2013 and August 2018. The primary outcome was VTE prophylaxis, and exposures of interest included acute and chronic bleeding. Medical records were parsed electronically for covariables, and logistic regression was used to assess factors associated with VTE prophylaxis. Results: There were 22, 499 patients studied, including 474 (2%) with IBD. Patients with IBD were less likely to be placed on VTE prophylaxis (79% with IBD, 87% without IBD), particularly if hematochezia was present (57% with hematochezia, 86% without hematochezia). Among patients with IBD, admission to a medical service and hematochezia (adjusted odds ratio 0.27; 95% CI, 0.16–0.46) were among the strongest independent predictors of decreased VTE prophylaxis use. Neither hematochezia nor VTE prophylaxis was associated with increased blood transfusion rates or with a clinically significant decline in hemoglobin level during hospitalization. Conclusion: Hospitalized patients are less likely to be placed on VTE prophylaxis if they have IBD, and hematochezia may drive this. Hematochezia appeared to be minor and was unaffected by VTE prophylaxis. Education related to the safety of VTE prophylaxis in the setting of minor hematochezia may be a high-yield way to increase VTE prophylaxis rates in patients with IBD. Video Abstract: